139k views
1 vote
Will give 100pts for this question

Will give 100pts for this question-example-1
User Jon Thoms
by
4.3k points

2 Answers

2 votes

Answer:

-3

Explanation:

Lucky guess?

User Marchelbling
by
5.0k points
5 votes

Answer:

-3

Solution,


\frac{24 {x}^(2) + 25x - 47}{ax - 2} = - 8x - 3 - (53)/(ax - 2) \\ \frac{24 {x}^(2) + 25x - 47 }{ax - 2} = (( - 8x - 3)(ax - 2) - 53)/(ax - 2) \\ 24 {x}^(2) + 25x - 47 = - 8a {x}^(2) + (16 - 3a)x - 47 \\

Equating coefficients from both side:


- 8a = 24 \\ a = ( 24)/( - 8) \\ a = - 3

Hope this helps..

good luck on your assignment..

User Peter Friese
by
5.1k points